Macromastia of pregnancy: A unique presentation of this rare clinicohistopathological entity - Sarda, Anil K; Kulshreshta, Vishal N; Bhalla, Shweta A; Singh, Lakhwinder; Chaturvedi, Uma K (Indian Journal of Plastic Surgery, 2004)
The present case is a unique presentation of a patient who developed a small lump in her breast during her first pregnancy but it was only during her third pregnancy that it increased in size and became a huge fungating mass. Although, gigantic sizes of this pathologic entity have been reported, the present case had the involved breast hanging till below the inguinal ligament and required sling to support the breast. Since the pre-operative diagnosis was suggestive of cystosarcoma phylloides, no attempt at reconstructive surgery was contemplated.
Keywords: Breast; macromastia